Distribution and Diversity of Comammox Nitrospira in Coastal Wetlands of China - Sun, Dongyao; Tang, Xiufeng; Zhao, Mengyue; Zhang, Zongxiao; Hou, Lijun; Liu, Min; Wang, Baozhan; Klümper, Uli; Han, Ping (Frontiers in Microbiology, 2020)
Complete ammonia oxidizers (comammox), able to individually oxidize ammonia to nitrate, are considered to play a significant role in the global nitrogen cycle. However, the distribution of comammox Nitrospira in estuarine tidal flat wetland and the environmental drivers affecting their abundance and diversity remain unknown. Here, we present a large-scale investigation on the geographical distribution of comammox Nitrospira along the estuarine tidal flat wetlands of China, where comammox Nitrospira were successfully detected in 9 of the 16 sampling sites. The abundance of comammox Nitrospira ranged from 5.19×103 to 8.33×104 copies/g, 2.21 to 5.44 folds lower than canonical ammonia oxidizers: ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA). Phylogenetic analysis based on the alpha subunit of the ammonia monooxygenase encoding gene (amoA) revealed that comammox Nitrospira Clade A, mainly originating from upstream river inputs, accounts for more than 80% of the detected comammox Nitrospira, whereas comammox Nitrospira clade B were rarely detected. Comammox Nitrospira abundance and dominant comammox Nitrospira OTUs varied within the estuarine samples, showing a geographical pattern. Salinity and pH were the most important environmental drivers affecting the distribution of comammox Nitrospira in estuarine tidal flat wetlands. The abundance of comammox Nitrospira was further negatively correlated with high ammonia and nitrite concentrations. Altogether, this study revealed the existence, abundance and distribution of comammox Nitrospira and the driving environmental factors in estuarine ecosystems, thus providing insights into the ecological niches of this recently discovered nitrifying consortium and their contributions to nitrification in global estuarine environments.